A secure blockchain-based web application voting system / Adib Farhan Sayuti - Sayuti, Adib Farhan (2019)
In almost every university, election for Student Representative Council is done through voting system. The purpose of the election is for better management and communication between the student and University. However, the voting process itself can sometimes be manipulated and problems such as voter fraud can happen. This could lead to spoofing the results and causing tainted ballot. The objectives of the Secure Blockchain-based Web Application Voting System are to design and develop a web application blockchain-based voting system that can enable a secure online voting and terminate all possible fraud in voting process. This system will use student identification for their own unique identification. By using the blockchain-based system, the project will have full transparency of the voting process thus avoiding the result spoofing. It is expected that from the result, this web-based system may eliminate the problem in voting process and secure the online voting system.